The lacI shuttle: rapid analysis of the mutagenic specificity of ultraviolet light in human cells. - Lebkowski, J S (1985)
A system has been devised that allows the effect of mutagens acting in human cells to be readily analyzed at the DNA sequence level. The bacterial gene lacI, carried on a shuttle vector, is introduced into human tissue culture cells by transfection and allowed to replicate in the cell nucleus. Twenty-four to 48 hr after transfection, the cells are exposed to a mutagen. After 1-2 days of further replication, vector DNA is purified and transfected back into Escherichia coli for scoring and analysis of mutations in lacI. The nucleotide sequence changes for 53 UV light-induced mutations have been deduced in this way. Most of the mutations are transitions and occur at pyrimidine-pyrimidine sequences. The mutagenic specificity observed closely resembles that of UV light in E. coli, suggesting that human and bacterial cells respond similarly to damage from UV light. Use of the lacI shuttle in this way should permit determination of the mutagenic specificity of a wide range of mutagens and carcinogens in human cells.